Gestão por competências: um estudo exploratório em uma instituição pública não-estatal qualificada como organização social - Antônio de Pádua Araujo (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2007)
The aim of this article is to analyze the manner how a non-state, qualified as social organization, deals with its own corporative competences and individual ones, seeking to make possible to set its strategic options, and also to analyze the manner how human resource management field drives the process of creating and developing these kind of competences. An empiric research, with an exploratory character, was made in Instituto Centro de Ensino Tecnológico that acts in the field of professional education and technological development, in which the necessary data to reach the previously objects were gotten from. The bibliographical references is mainly composed by the concepts that holds the boards of discussions about competent management. The data required was obtained trough the use of questionnaires, interviews, documental analysis and meetings with all the agents involved in the research. With this research, it hopes to set a better comprehension of a theme that has a lack of studies of this nature.